2020
DOI: 10.1186/s12912-020-00499-7
|View full text |Cite
|
Sign up to set email alerts
|

Child health nurse perceptions of using confident body, confident child in community health: a qualitative descriptive study

Abstract: Background Confident Body, Confident Child (CBCC) is an innovative, evidence-based program providing parenting strategies to promote healthy eating, physical activity and body satisfaction in children aged 2–6 years. This study aimed to explore Child Health Nurse (CHN) experiences with using CBCC in their community health clinics with parents of young children. This work is part of a larger study involving tailoring, implementing and evaluating CBCC in a community child health setting. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
4
0
0
Order By: Relevance
“…Our study found CHNs highly valued the MCM content and resources, with both the qualitative and quantitative data reflecting this result. Our findings are consistent with previous research that implemented an evidenced-based program providing preventive strategies for child health nurses to use with parents of children 2–6 years old [ 31 ]. This study revealed CHNs valued the content and believed early intervention and prevention of eating problems was a core part of their work in a community child health service [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found CHNs highly valued the MCM content and resources, with both the qualitative and quantitative data reflecting this result. Our findings are consistent with previous research that implemented an evidenced-based program providing preventive strategies for child health nurses to use with parents of children 2–6 years old [ 31 ]. This study revealed CHNs valued the content and believed early intervention and prevention of eating problems was a core part of their work in a community child health service [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with previous research that implemented an evidenced-based program providing preventive strategies for child health nurses to use with parents of children 2–6 years old [ 31 ]. This study revealed CHNs valued the content and believed early intervention and prevention of eating problems was a core part of their work in a community child health service [ 31 ]. Interestingly, one of the recommendations from CHNs in this study was to start having conversations with parents when their children were younger; when they were transitioning to solids was deemed an appropriate time.…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings are consistent with previous research that implemented an evidenced-based program providing preventive strategies for child health nurses to use with parents of children 2-6 years old (31). This study revealed CHNs valued the content and believed early intervention and prevention of eating problems was a core part of their work in a community child health service (31). Interestingly, one of the recommendations from CHNs in this study was to start having conversations with parents when their children were younger; when they were transitioning to solids was deemed an appropriate time.…”
Section: Acceptabilitysupporting
confidence: 91%
“…Our study found CHNs highly valued the MCM content and resources, with both the qualitative and quantitative data re ecting this result. Our ndings are consistent with previous research that implemented an evidenced-based program providing preventive strategies for child health nurses to use with parents of children 2-6 years old (31). This study revealed CHNs valued the content and believed early intervention and prevention of eating problems was a core part of their work in a community child health service (31).…”
Section: Acceptabilitysupporting
confidence: 90%